PEMENUHAN KEBUTUHAN PERSONAL HYGIENE PADA ANAK: LITERATURE REVIEW - Gusti Putu Ayu Febri Sinta Dewi; Mochamad Heri (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Background: One of the human needs that support health is personal hygiene. The period of growth and development in children is the most appropriate time to practice personal hygiene. Likewise, health problems that often occur in early childhood are related to personal hygiene. Getting used to living clean and healthy in children should be done as early as possible because the habits that are implanted will affect the child's healthy behavior. One of the importance of personal hygiene is to minimize the occurrence of a disease caused by microorganisms found in various places. Purpose: This literature review aimed to identify, and analyze the journal related to topics that described the implementation of the efforts to fulfillment of personal hygiene in the children. Method: A literature review with PICO analysis accompanied by evidence-based practice was carried out as the method of this study particularly by analyzing 10 article journals (8 national journals and 2 international journals). The literature criteria used were the publication of articles in the last three years, from 2017 to 2020, and the articles with accessible free full text in Google Scholar, and PubMed. Results: the discussion in this study could help readers and nurses to understand that the fulfillment of personal hygiene in children is very important because it can provide stimulation/positive impact in improving the health status of children, and in order to avoid various kinds of harmful microorganisms that cause disease.